Investigating The Problems Of Translating Idiomatic Expressions From English Into Arabic In News Articles From Reuters News Agency - Khalaf, Muthana Hameed (2010)
Translating English texts that comprise idiomatic expressions represent one of the most challenging tasks for translators to accomplish. Thus, the present study is concerned with the problems of translating idiomatic expressions from English as the SL into Arabic as the TL in Reuters news agency and sheds light on the most appropriate method for translating idiomatic expressions. The corpus of this study consists of 50 newspaper articles that are taken from Reuters news agency. The theoretical framework for the study is adapted from the works of Delisle (1988).